KEPEMIMPINAN TRANSFORMASIONAL DAN PENGARUHNYA PADA BUDAYA PEMBELAJARAN ORGANISASI DALAM MENINGKATKAN KINERJA SDM - Stiyoaji, Kirun; Radisha, Raflian Alviki; Muttaqin, Ahmad Zainul; Rahman, Restu Afrianto; Pratiwi, Ratih (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
This study uses an associative explanatory approach to examine the relationship between transformational leadership, organizational culture that supports learning, and the performance of DPRD Experts at the Secretariat of the Central Java Provincial Council. The study population involved 120 experts, with the entire population sampled through the census method. Primary data were collected using a questionnaire with a Likert scale of 1 to 5 and analyzed using the Partial Least Square (PLS) method. The results of the analysis show that all proposed hypotheses are accepted. This indicates a positive and significant relationship between transformational leadership, organizational learning culture, and expert performance. The more effective the implementation of transformational leadership, the better the development of learning culture in the organization. A strong learning culture also significantly improves expert performance. This finding underscores the importance of transformational leadership in promoting continuous learning in the organizational environment. Effective leadership not only strengthens the learning culture, but also has a direct impact on improving overall HR performance. In other words, good implementation of transformational leadership can be a catalyst for creating a productive and innovative work environment, which ultimately supports the achievement of organizational goals.